“The finding aid is the first thing that people see, we don’t want to put anyone off viewing the collection”: how practitioners navigate queerness in finding aids - Wagner, Travis L.; Allgood, Evan M.; Caballero, Mateo (Archival science, 2025)
This paper reports on findings from semi-structured interviews with 29 archival practitioners who work on the creation and maintenance of finding aids related to LGBTQIA+ archival materials. The paper highlights key findings focused on how practitioners navigated the design and use of queer-specific finding aids with an emphasis on the tensions between historical terminology, various LGBTQIA+ identities, and the contemporary expectations of queer-inclusive language. Additionally, findings highlight how practitioners rely on their own personal embodied knowledge in conjunction with the knowledge of donors and queer community members to ensure ethical and affirming archival description. In particular, this emphasis on embodied knowledge highlighted a shift in ethical practice which, for many participants, departed from traditional archival praxis and required them to change their approach to the construction of finding aids. Finally, findings emphasize the importance of queer tools such as the Homosaurus and other queer reparative description initiatives, given their community-vetted nature. The paper concludes by identifying both theoretical and practical implications for the work and suggests future directions for research based on findings.